2020
DOI: 10.3390/ijms21082934
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Proteomic Characterization of Cutaneous Melanoma Ectosomes Reveals the Presence of Cancer-Related Molecules

Abstract: Cutaneous melanoma (CM) is an aggressive type of skin cancer for which effective biomarkers are still needed. Recently, the protein content of extracellular vesicles (ectosomes and exosomes) became increasingly investigated in terms of its functional role in CM and as a source of novel biomarkers; however, the data concerning the proteome of CM-derived ectosomes is very limited. We used the shotgun nanoLC–MS/MS approach to the profile protein content of ectosomes from primary (WM115, WM793) and metastatic (WM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…1c) showed several components with different dimension. The mean size of this distribution was 291.5 ± 4.3 nm according to the previous observations [31]. TEM analysis revealed, as evident in Fig.…”
Section: Isolation and Characterization Of Melanoma-derived Exossupporting
confidence: 81%
“…1c) showed several components with different dimension. The mean size of this distribution was 291.5 ± 4.3 nm according to the previous observations [31]. TEM analysis revealed, as evident in Fig.…”
Section: Isolation and Characterization Of Melanoma-derived Exossupporting
confidence: 81%
“…So far, similar studies have not been conducted on the latter population of EVs. Nevertheless, ectosomes can also contain a specific protein profile enriched in cancer biomarkers; this was demonstrated in our previous studies for melanoma [19,20] as well as other studies on breast [21], head and neck [22], and ovarian cancer [23]. In the present study we used a liquid chromatography coupled with tandem mass spectrometry-based (nanoLC-MS/MS) proteomic approach to investigate the protein content of ectosomes released in vitro by T-24 UBC and HCV-29 normal ureter epithelial cells.…”
Section: Introductionmentioning
confidence: 71%
“…We found that LVF samples had the highest intensity of Hsp70 and CD63 bands, while the Arf-6 and CD81 bands had similar low intensity in the samples isolated by all tested methods. Ectosome samples are usually enriched in Arf-6, the protein involved directly in the shedding of plasma membrane-derived EVs, but not in exosome biogenesis [ 24 ]. In our study, relatively low expression of Arf-6 in comparison to the exosome marker CD63 was observed, showing that exosome proteins dominated in all samples.…”
Section: Discussionmentioning
confidence: 99%
“…Differential centrifugation was performed according to the previously described protocol [ 24 ]. After the three preparatory centrifugations, samples were transferred to 50 (mL) polycarbonate centrifuge tubes and centrifuged for 20 (min) at 18,000 (g) at 4 (°C) (Sorvall LYNX 6000 Superspeed Centrifuge, Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%